China’s Quiet Stake inPost-Assad Syria - Ismail, A. (The Diplomat, 2025)
China’s engagement with Syria is entering a new phase after the fall of Bashar al-Assad, but Beijing is moving with calculated restraint. In mid-November 2025, Syrian Foreign Minister Asaad al-Shaibani visited Beijing and met Chinese Foreign Minister Wang Yi, signaling Damascus’s interest in Chinese investment and China’s willingness to keep channels open with Syria’s transitional authorities. This article argues that China’s stake in post-Assad Syria is real but narrower than many assume. Beijing is not positioning itself as Syria’s primary patron. Instead, it is pursuing a cautious approach that protects three interests: limiting the security threat posed by foreign fighters, preserving China’s diplomatic posture on sovereignty and non-interference, and keeping economic options open without committing significant capital while sanctions risk, corruption risk, and governance uncertainty remain high. The timing matters. The UN Security Council removed sanctions on Syria’s transitional president and interior minister, with China abstaining and explicitly pointing to counterterrorism concerns, including the Eastern Turkistan Islamic Movement (ETIM). Days later, at the Security Council, China’s UN ambassador emphasized foreign terrorist fighters as a priority concern and urged Syria to act against designated groups, again highlighting ETIM. This emphasis signals a core reality: for Beijing, Syria is a counterterrorism file first and an economic opportunity second. On the economic front, Damascus is seeking reconstruction partners and has pointed to deals such as the free-zone investment memorandum involving Fidi Contracting. The article uses this case to show why China is likely to proceed via smaller, lower-risk entry points before any large-scale reconstruction role becomes plausible. The piece will conclude by explaining what would change China’s calculus: measurable security consolidation, more explicit rules for investment protection, and a pathway around sanctions exposure. Until then, China’s Syria policy will remain defined by cautious engagement rather than bold bets.